How can miscanthus fields be reintegrated into a crop rotation?. Issue 11 (25th July 2019) - Mangold, Anja; Lewandowski, Iris; Kiesel, Andreas
Abstract: The bioeconomy, with its aim of replacing fossil by biobased resources, is increasingly focusing on biomass production from perennial crops, such as miscanthus. To date, research on miscanthus has explored a number of cultivation aspects; however, one major issue has not yet been addressed: How can former miscanthus fields be reintegrated into a crop rotation? This encompasses the questions of which following crop most efficiently suppresses resprouting miscanthus and what happens to the soil nitrogen content after a miscanthus removal. This study aimed to answer both questions. For this purpose, four spring crops (ryegrass, rapeseed, barley, maize) and fallow as control were cultivated after a Miscanthus sinensis removal. To test the effect of the removal on soil nitrogen content, each spring crop (excluding fallow) was divided into fertilized and unfertilized plots. After the spring crop harvest, winter wheat was cultivated to clarify which spring crop had most efficiently suppressed the resprouting miscanthus. The results indicate that fertilized crops had 35% less miscanthus biomass per hectare than unfertilized crops, probably due to the higher plant density and/or better development of the fertilized crops during the growing season. The soil mineral nitrogen (Nmin ) content was found to increase during the vegetation period following the miscanthus removal (average +14.85 kg/ha), but was generally on a low level. We conclude that nitrogen from miscanthus residues is partly fixed in organic matter and is thus not plant‐available in the first cropping season. As some nitrogen is supplied by the decomposition of miscanthus residues, our results suggest that the crop cultivated after a miscanthus removal requires less fertilization. Of all the follow‐on spring crops tested, maize coped with the prevailing soil conditions and resprouting miscanthus most efficiently, resulting in satisfactory yields, and thus seems to be a suitable crop for cultivation after miscanthus. Abstract : This study aimed to answer two questions: (i) Which following crop suppresses most efficiently resprouting miscanthus? (ii) What happens to the soil nitrogen content after a miscanthus removal? For this purpose, four spring crops (ryegrass, rapeseed, barley, maize) and fallow as control were cultivated after a Miscanthus sinensis removal. To test the effect of the removal on soil nitrogen content, each spring crop (excluding fallow) was divided into fertilized and unfertilized plots. After the spring crop harvest, winter wheat was cultivated to clarify which spring crop had most efficiently suppressed the resprouting miscanthus.